Candida albicans in patients with denture stomatitis of the Center for the Elderly Adult, Chiclayo, Perú - Álvarez Chupillón, Hugo Antonio (2017)
Objective: Determine if there is an association between the presence of Candida albicans and the denture stomatitis type in patients who attend to the aged center of Chiclayo – July 2012. Materials and Methods: 58 patients with removable dental prostheses diagnosed clinically with denture stomatitis were evaluated. A palatal mucosal swab was performed and then cultured directly in the medium of the CHROMagar Candida culture at 37 ° C for 48 hours. The crop that tested positive for Candida albicans were submitted to germ-tube testing. Results: A total of 35 (60%) cultures tested positive for Candida albicans, with grade III of denture stomatitis being 100% associated with Candida albicans (n = 3), grade II presented 70.8% (n=17). The total prosthesis was more involved in the presence of Candida albicans (65.5%) with no statistical significance, p= 0.591. Conclusions: There is association between the denture stomatitis and Candida albicans.Key words: Candida albicans; denture st